HUKUKI AILE KARARNAMESI: Reformasi dan Konstitusionalisasi Hukum Keluarga Islam di Turki - Chamim Tohari (Jurnal Penelitian, 2017)
This research focused to the study about Hukuki Aile Kararmnamesi (HAK) in the historical aspect which is specialized to answer several main problems about background, characteristic of the fiqh thought, implementation as a legal constitution in Turkey, the methods of codification, and its role and existence between legislation of the family secular law in the early modern state of Turkey. The researcher use a historical analysis approach as method to describe the result of this research. The result of this research were: (1) The background of the codification of Islamic Family Law in Turkey is a condition of the Ottoman empire which had reformation in the law field in the Sultan Abdul Hamid period. Cause of the reformation of law is a pressure to the modernization and secularization by West states to the countries under Ottoman’s authority. Afterwards, the universal, unbounded to the one or more of mazhab thoughts, and realistic maybe can be mentioned as the characteristic of the HAK book; (2) The method of codification is Talfiq method. It is using several opinions from the muslem scholars in the difference sects, then choose one of the most relevan opinion of law which is needed by the citizen; and (3) Untill now the book (HAK) still implementated by the moslem society in the modern state of Turkey together with the legislation of The Civil Code, a secular family law as substitute of this book since the year 1926 ago.